On the determinants and effects of corporate tax transparency: Review of an emerging literature - Raphael Müller; Christoph Spengel; Heiko Vay (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
In response to discussions about large multinational enterprises' tax planning activities, legislators around the world have adopted numerous regulations to increase corporate tax transparency. New settings and datasets have spurred empirical research in recent years. Our paper presents a review of this emerging literature on corporate tax transparency. To this end, we first propose a framework to structure the diverse landscape of tax-related disclosures. Second, we elaborate on the conceptual underpinnings of tax transparency by drawing on established theories from financial accounting and CSR reporting research. Third, we survey empirical evidence on corporate tax transparency. We classify the findings into (i) determinants of firms' tax disclosure decisions, (ii) informativeness of different kinds of tax-related disclosure, and (iii) effects of increased tax transparency on firms and their stakeholders. Finally, we synthesize the main inferences and offer suggestions for future research.
Keywords: F23; G38; H25; H26; M14; M41; 330; tax transparency; tax disclosure; tax planning; literature review